PENDEKATAN RAMAH DEMENSIA DALAM PERANCANGAN INTERIOR KAMAR MANDI BAGI LANSIA DI BANDUNG GERIATRIC CENTER - Austranti Yuwono, Astrid; Setyoningrum, Yunita; Maximillian, Arnold; Nathania Suhanjoyo, Shirly (Jurnal Abdimas Bina Bangsa, 2025)
Bandung Geriatric Center (BGC) is a clinic that focuses on services for the elderly. Procurement of toilets or self-cleaning facilities is of immediate urgency because there are several major problems with existing building toilets so they must be redesigned considering existing ergonomics and accessibility standards. Collaboration of Interior Design, Architecture, Visual Communication Design, and Medicine expertise at Maranatha Christian University seeks to re-design existing toilets and bathrooms at BGC, considering safety, efficiency, and comfort standards for the conditions of elderly patients, as well as providing education for the public about the importance of special facilities for the elderly, with a dementia-friendly design approach. This cross-expertise collaboration dedication has produced ideas based on comprehensive scientific knowledge. Therefore, this service can be a simple movement but provides good benefits for BGC which provides clinic facilities and deals directly with elderly users, as well as benefits for the community through educational leaflets about preventing the risk of falls in the elderly.